Exploring the global innovation systems perspective by applying openness index to national systems of innovation - Aram Cho; Sangook Park (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This paper raises the question of whether global innovation systems (GIS), the expanded networks of actors beyond national boundaries, could be a new sibling of innovation systems perspectives. We argue that in today's globalized world, it is idoneous to analyze innovation activities in a global context rather than a national or regional one. To confirm this argument, first, previous research is reviewed to understand how the GIS perspective has emerged and what different aspects have enabled these discussions. Distinct gaps from a body of literature are identified, such as the lack of a united definition, leading causes, and empirical evidence of GIS. With this understanding of the GIS perspective's background, this research aims to overcome the challenge of filling out these gaps using two-stage approaches. The first approach suggests three building blocks of the GIS perspective (global institutions, global actors and networks, and a global knowledge-base). Using the open innovation concept, the second approach measures the openness of national innovation systems (NIS) of the OECD DAC (Development Assistance Committee) member countries to represent the tangibility of the GIS perspective. The paper concludes that the GIS approach would provide us with a valuable viewpoint for analyzing current innovation activities in today's globalized economy as the form of GIS perspective is observed when measured.
Keywords: 650; global innovation systems (GIS); globalization; institutional convergence; national innovation systems (NIS); open innovation; openness